Poverty and a practical ministry of liberation and development within the context of the traditional Venda concept of man - Van Deventer, Wilhelm Visser (University of Limpopo, 1989)
Refer to the document
Thesis (M. A. (Biblical Studies)) -- University of the North, 1989
Keywords: Poverty; Dutch Reformed Church; Poor people; Venda people; Poverty -- Religious aspects -- Christianity; Man (Theology); Church work with the poor -- South Africa; Venda (Africa people)